Navigation rules international-inland (Skyhorse Pub., 2011)
For anyone who owns a boat, this is the handbook you need to own. Included are all of the official government rules and regulations that must be followed by anyone out on the water. This book will prepare you for head-on situations, avoiding collisions, using, distress signals, and will inform you of all the up-to-date water regulations. Whether you're in a jam or just relaxing at sea, Navigation Rules will teach and prepare you for anything and everything you may encounter while on your boat.